Metabolic syndrome and cognitive decline in French elders: the Three-City Study - Raffaitin, C; Féart, C; Le Goff, M; Amieva, H; Helmer, C; Akbaraly, T N; Tzourio, C; Gin, H; Barberger-Gateau, P (Neurology, 2011)
To examine associations between metabolic syndrome (MetS) and its individual components with risk of cognitive decline on specific cognitive functions. Participants were 4,323 women and 2,764 men aged 65 and over enrolled in the longitudinal Three-City Study. Cognitive decline, defined as being in the worst quintile of the distribution of the difference between baseline score and either 2- or 4-year follow-up, was assessed by the Mini-Mental State Examination (MMSE, global cognitive function), the Isaacs Set Test (IST, verbal fluency), and the Benton Visual Retention Test (BVRT, visual working memory). MetS was defined by National Cholesterol Education Program-Adult Treatment Panel III criteria (at least 3 of 5 cardio-metabolic abnormalities: hypertension, high waist circumference, hypertriglyceridemia, low high-density lipoprotein [HDL] cholesterol, hyperglycemia). Proportional hazards models were adjusted for age, gender, educational level, center, baseline cognitive score, APOE4 genotype, and other potential confounders. MetS at baseline was associated with an increased risk of cognitive decline on MMSE (hazard ratio [HR] = 1.22 [1.08-1.37]; p = 0.001) and BVRT (HR = 1.13 [1.01-1.26]; p = 0.03) but not on IST (HR = 1.11 [0.95-1.29]; p = 0.18). Among MetS components, hypertriglyceridemia and low HDL cholesterol were significantly associated with higher decline on MMSE; diabetes, but not elevated fasting glycemia, was significantly associated with higher decline on BVRT and IST. MetS as a whole and several of its components had a negative impact on global cognitive decline and specific cognitive functions in older persons.